Sweet syndrome as an adverse reaction to tyrosine kinase inhibitors: A review. Issue 1 (5th November 2020) - Yang, Jason J.; Maloney, Nolan J.; Nguyen, Kevin A.; Worswick, Scott; Smogorzewski, Jan; Bach, Daniel Q.
Abstract: Tyrosine kinase inhibitors are a class of targeted anticancer drugs that inhibit cancer cell proliferation by inactivating proteins involved in signal transduction cascades. Various cutaneous adverse events have been observed after tyrosine kinase inhibitor administration, including Sweet syndrome. We queried the PubMed database to identify 14 cases of Sweet syndrome thought to be secondary to tyrosine kinase inhibitors. Tyrosine kinase inhibitor‐induced Sweet syndrome had a median of 2 months latency following drug administration. All cases but one had morphologic features classic for Sweet syndrome (erythematous and tender papules, plaques, or nodules). All cases also had classic histopathologic findings (dermal neutrophilic infiltrate without vasculitis or necrosis). Using diagnostic criteria for drug‐induced Sweet syndrome and the Naranjo Drug Reaction Probability Scale for a drug‐induced cutaneous eruption, we found that six cases favored a drug‐induced etiology over malignancy, two cases favored a malignancy‐associated Sweet syndrome, and the remaining eight met drug‐induced Sweet syndrome criteria but had low Naranjo scores. Nine cases resulted in medication discontinuation, while five cases continued anticancer therapy and were treated only with corticosteroids with quick resolution of skin lesions. Dermatologists should be aware of this adverse cutaneous reaction to tyrosine kinase inhibitors and should treat on a case‐by‐case basis, though limited evidence in this review suggests that oncologic therapy may safely be continued with prompt corticosteroid treatment.